The genus Buccinanops: A Model for Eye Loss in Caenogastropods - Averbuj, Andres (2008)
The genus Buccinanops (d'Orbigny, 1841) (Caenogastropoda, Nassarriidae) is endemic to the SW Atlantic Ocean, and the name implies no eyes, due to the lack of visible eyes in adults. We recognize for the first time the occurrence of eyes during several developmental stages within Buccinanops. Eye spots in Buccinanops cochlidium (Dillwyn, 1817) were observed during intracapsular development and in hatchlings and juveniles. Eyes were histologically confirmed in embryonic cephalic tentacles; they were comprised of sensory cells, supportive cells, a lens, and an optic nerve cord. The ontogenetic history of the eyes of B. cochlidium is discussed.